2021 IEEE International Conference on Robotics and Automation (ICRA) 2021
DOI: 10.1109/icra48506.2021.9562009
|View full text |Cite
|
Sign up to set email alerts
|

Active Inference for Integrated State-Estimation, Control, and Learning

Abstract: This work presents an approach for control, stateestimation and learning model (hyper)parameters for robotic manipulators. It is based on the active inference framework, prominent in computational neuroscience as a theory of the brain, where behaviour arises from minimizing variational freeenergy. The robotic manipulator shows adaptive and robust behaviour compared to state-of-the-art methods. Additionally, we show the exact relationship to classic methods such as PID control. Finally, we show that by learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…General introduction and tutorial [50], [5], Derivations for robot control [13], [17] Relationship with classical control [51], [18] Relationship with optimal control [52], [53] Discrete Active Inference [54] RL and active inference [55], [25] State estimation [56], [9] Predictive processing [57], [58] Human Robot Interaction [45] Neuroscientific foundations [1], [59] Fig. 2.…”
Section: Topic Referencesmentioning
confidence: 99%
See 4 more Smart Citations
“…General introduction and tutorial [50], [5], Derivations for robot control [13], [17] Relationship with classical control [51], [18] Relationship with optimal control [52], [53] Discrete Active Inference [54] RL and active inference [55], [25] State estimation [56], [9] Predictive processing [57], [58] Human Robot Interaction [45] Neuroscientific foundations [1], [59] Fig. 2.…”
Section: Topic Referencesmentioning
confidence: 99%
“…2) With precision learning: The authors in [18] presented an evolution of [17] by including online parameters learning for controller auto-tuning. The authors demonstrated how the minimization of the VFE produces effective state-estimation, control for robotic manipulators.…”
Section: B Adaptive Controlmentioning
confidence: 99%
See 3 more Smart Citations